MicroRNAs Are Intensively Regulated during Induction of Somatic Embryogenesis in Arabidopsis - Szyrajew, Katarzyna; Bielewicz, Dawid; Dolata, Jakub; Wójcik, Anna M.; Nowak, Katarzyna; Szczygieł-Sommer, Aleksandra; Szweykowska-Kulinska, Zofia; Jarmolowski, Artur; Gaj, Małgorzata D. (Frontiers in Plant Science, 2017)
Several genes encoding transcription factors (TFs) were indicated to have a key role in the induction of somatic embryogenesis (SE), which is triggered in the somatic cells of plants. In order to further explore the genetic regulatory network that is involved in the embryogenic transition induced in plant somatic cells, micro-RNA (miRNAs) molecules, the products of MIRNA (MIR) genes and the common regulators of TF transcripts, were analysed in an embryogenic culture of Arabidopsis thaliana. In total, the expression of 190 genes of the 114 MIRNA families was monitored during SE induction and the levels of the primary (pri-miRNAs) transcripts vs the mature miRNAs were investigated. The results revealed that the majority (98%) of the MIR genes were active and that most of them (64%) were differentially expressed during SE. A distinct attribute of the MIR expression in SE was the strong repression of MIR transcripts at the early stage of SE followed by their significant up-regulation in the advanced stage of SE. Comparison of the mature miRNAs vs pri-miRNAs suggested that the extensive post-transcriptional regulation of miRNA is associated with SE induction. Candidate miRNA molecules of the assumed function in the embryogenic response were identified among the mature miRNAs that had a differential expression in SE, including miR156, miR157, miR159, miR160, miR164, miR166, miR169, miR319, miR390, miR393, miR396 and miR398. Consistent with the central role of phytohormones and stress factors in SE induction, the functions of the candidate miRNAs were annotated to phytohormone and stress responses. To confirm the functions of the candidate miRNAs in SE, the expression patterns of the mature miRNAs and their presumed targets were compared and regulatory relation during SE was indicated for most of the analysed miRNA-target pairs. The results of the study contribute to the refinement of the miRNA-controlled regulatory pathways that operate during embryogenic induction in plants and provide a valuable platform for the identification of the genes that are targeted by the candidate miRNAs in SE induction.